Proses Penyelesaian Pembagian Harta Bersama Suami Isteri Dalam Perkawinan Setelah Bercerai (Studi Kasus di Pengadilan Agama Karanganyar) - Ayezha, Putri Lita, Nuswardani, S.H., S.U (2016)
Many life of marriages that ended in divorce. The division of joint property in marriage being the other issues that arises after the divorce happened. Issues concerning joint property often occur between ex-husband and ex-wife about the division of joint property in marriage. This type of research is normative juridical approach. Respondent in the study is the judges in Pengadilan Agama Karanganyar. The conclusion of this study are: (1) There are three basic law that can be used to the judges for completing to the resolutions process of division of joint property in marriage there are, KUHPerdata, Common Law and KHI. (2) The basic consideration for judges is by judjing from the process of proof in the trial, which is the defendant can prove his denial statement, then the judges deciding which is devided only including the joint property and each ex-husband and ex-wife is entitled to the half of the joint property, based on Pasal 97 KHI.